Construction of territory: elements that conceal memory and identity in the Tucapel Bajo neighbourhood in Concepcion (Revista LIDER, 2020)
The purpose of this text is to contribute to the reflection on the process of construction of  territory, emphasizing the concepts of memory and identity in a popular neighbourhood within an urban poverty context, starting from the experience of Tucapel Bajo neighbourhood in Concepción, Chile. These analyses of the process of construction of territory, are connected with the concept of “lived space”, incorporating in this reflection the concept of “anthropologic place” coined by the French anthropologist Marc Augé.